FridaysForFuture Rappresentazioni sociali del cambiamento climatico e pratiche d'uso dei social media - Belotti, Francesca (Teorie sociologiche e trasformazioni sociali, 2022)
The book addresses the theme of youth climate activism building on the experience of FridaysForFuture activists and analyzing both their social representations of climate change and their social media usage practices. It accounts for the results of a qualitative research carried out with(in) the Roman group of the movement, adopting a solidarity-based epistemic stance that invites reflections both on activism and research practices. Drawing upon social representations theory, the authors analyze how the "Fridays" perceive climate change: as a socio-ecological crisis that comes from afar and has repercussions on the future, as something that affects everything and everyone; but also, as a generational problem whose environmental, social, and economic costs will be paid mainly by young people. On the other hand, guided by the literature on digital activism, the authors explore the way in which the activists inhabit social media: as constitutive environments of activism, where political and media practices define each other; but also, as environments that belong to young people and are characterized by age-specific communication styles. The two experiences related to climate change and the political usages of social media influence each other, giving rise to an unprecedented youth movement for the climate that can tell us about the transformations currently undergoing digital, environmental, and youth activism.